Toll-Like Receptors and Cytokines as Surrogate Biomarkers for Evaluating Vaginal Immune Response following Microbicide Administration - Sadhana M. Gupta; Clara C. Aranha; Madhu C. Mohanty; K. V. R. Reddy (Mediators of Inflammation)
Topical microbicides are intended for frequent use by women in reproductive age. Hence, it is essential to evaluate their impact on mucosal immune function in the vagina. In the present study, we evaluated nisin, a naturally occurring antimicrobial peptide (AMP), for its efficacy as an intravaginal microbicide. Its effect on the vaginal immune function was determined by localizing Toll-like receptors (TLRs-3, 9) and cytokines (IL-4, 6 , 10 and TNF-α) in the rabbit cervicovaginal epithelium following intravaginal administration of high dose of nisin gel for 14 consecutive days. The results revealed no alteration in the expression of TLRs and cytokines at both protein and mRNA levels. However, in SDS gel-treated group, the levels were significantly upregulated with the induction of NF-κB signalling cascade. Thus, TLRs and cytokines appear as sensitive indicators for screening immunotoxic potential of candidate microbicides.